Identifikasi Bakteri Dari Sampel Darah Pasien COVID-19 Di RSUD Ciawi Kabupaten Bogor - Safari, Wulan Fitriani; Wardhiati, Sri; Dewi, Almatin Puspa (Journal of Medical Laboratory Research, 2024)
Coronavirus Disease 2019 (COVID-19) is a disease caused by the Severe Acute Respiratory Syndrome Corona Virus 2 virus called SARSCov-2, this virus attacks the respiratory tract and creates a risk of infection in COVID-19 patients. Bacterial infections are known to complicate viral infections of the respiratory tract and are associated with worsening conditions in COVID-19 patients. The aim of this research is to identify bacteria from blood samples of COVID-19 patients at Ciawi Hospital, Bogor Regency. This type of research is quantitative descriptive which describes the types of bacteria from blood samples from COVID-19 patients. The samples in this study were patients who were confirmed (PCR) positive for COVID-19 who underwent blood culture microbiology examinations at Ciawi Regional Hospital. Data collection was carried out using the documentation study method. The research results showed that of the 243 COVID-19 patients who underwent blood culture examination, 63 samples showed positive results. In blood culture from 63 positive samples, 51 samples (80.9%) found Gram positive bacteria consisting of: S. hominis, S. haemolyticus, S. epidermidis, S. cohnii ureal, S. aureus, S. warneri and E. faecalis. There were 12 Gram Negative bacteria in blood culture (19.1%) consisting of A. baumannii, E. coli, Pseudomonas sp, K. pneumoniae, S. paucimobilis and E. aerogenes.